Gut microbiota and common gastrointestinal diseases: a bidirectional two-sample Mendelian randomized study - Qiu, Binxu; Shen, Zixiong; Yang, Dongliang; Qin, Xinxin; Ren, Wenyong; Wang, Quan (Frontiers in Microbiology, 2023)
Several recent studies have shown an association between gut microbiota and gastrointestinal diseases. However, the causal relationship between gut microbiota and gastrointestinal disorders is unclear.We assessed causal relationships between gut microbiota and eight common gastrointestinal diseases using Mendelian randomization (MR) analyses. IVW results were considered primary results. Cochrane's Q and MR-Egger tests were used to test for heterogeneity and pleiotropy. Leave-one-out was used to test the stability of the MR results, and Bonferroni correction was used to test the strength of the causal relationship between exposure and outcome.MR analyses of 196 gut microbiota and eight common gastrointestinal disease phenotypes showed 62 flora and common gastrointestinal diseases with potential causal relationships. Among these potential causal relationships, after the Bonferronicorrected test, significant causal relationships remained between Genus Oxalobacter and CD (OR = 1.29, 95% CI: 1. 13-1.48, P=2.5 × 10-4, q=4.20 × 10-4), and between Genus Clostridiumsensustricto1 and IBS (OR = 0.9967, 95% CI: 0.9944 -0.9991, P=1.2 × 10-3, q=1.56 × 10-3). Cochrane's Q-test showed no significant heterogeneity among the various single nucleotide polymorphisms (SNPs). In addition, no significant level of pleiotropy was found according to the MR-Egger.This study provides new insights into the mechanisms of gut microbiota-mediated gastrointestinal disorders and some guidance for targeting specific gut microbiota for treating gastrointestinal disorders.